Firm-Specific Determinants of Stock Prices in the Post-Pandemic Era - Ardyan Firdausi Mustoffa; Ika Farida Ulfah; Wijianto Wijianto (Owner : Riset dan Jurnal Akuntansi, 2025)
Purpose—This study aims to analyze the influence of firm-specific factors—specifically Cash Flow, Profitability, Firm Size, and Capital Structure—on the Stock Prices of consumer manufacturing firms listed on the Indonesia Stock Exchange (IDX). This sector is strategically vital due to its substantial contribution to the national Gross Domestic Product (GDP), yet its stocks frequently face challenges related to volatility and price decline, raising critical questions about which fundamental signals are most effectively received and acted upon by the market. Design/Methodology—Employing a multiple linear regression method, this research utilizes secondary data from annual financial reports covering the period 2019 to 2024. The novelty lies in its comprehensive simultaneous analysis of these four fundamental variables in this sector, specifically emphasizing the differential signaling effect between Cash Flow and Profitability. Findings—Partial test results indicate that Cash Flow from Investing Activities/CFI and Firm Size have a positive and significant effect on Stock Prices. This suggests that investors perceive Cash Flow as a more reliable signal of a company's financial health than Profitability, which was found to be partially insignificant. Simultaneously, all four variables collectively demonstrate a significant effect on Stock Prices. Conclusion—In the Indonesian market context, Cash Flow from Investing Activities/ CFI and Firm Size are the key factors that command the most attention from investors in their investment decision-making processes within the consumer manufacturing sector